ELONGATED HYPOCOTYL 5 promotes root growth by maintaining redox homeostasis and repressing oxidative stress response - Zhu, Xinxing; Liu, Lin; Yang, Liyun; Ma, Fei; Yang, Ting; Fu, Jing; Cui, Hongchang (Plant physiology (Bethesda), 2025)
Oxidative stress is a major threat to plant growth and survival. To understand how plants cope with oxidative stress, we carried out a genetic screen for Arabidopsis (Arabidopsis thaliana) mutants with altered response to hydrogen peroxide (H2O2) in root growth. Herein, we report the characterization of one of the hypersensitive mutants obtained. This mutant had slightly shorter roots in normal growth medium, and this phenotype became more pronounced in H2O2-containing medium. Through genome-wide resequencing and complementation experiments, we identified the gene with the causal mutation as ELONGATED HYPOCOTYL 5 (HY5). Histochemical staining revealed that the apical meristem of hy5 roots had an elevated level of H2O2 but a lower level of superoxide. In further experiments, we showed that genes involved in redox homeostasis and oxidative response were altered in hy5 roots and that MYB DOMAIN PROTEIN 30 (MYB30), GLUTATHIONE S-TRANSFERASE PHI 2 (GSTF2) and GLUTATHIONE S-TRANSFERASE TAU 19 (GSTU19) are directly repressed by HY5. Interestingly, overexpression of MYB30, a master regulator of the oxidative stress response, exacerbated the root growth defect in hy5, whereas knocking it down by RNAi largely rescued the mutant’s hypersensitivity to H2O2 without affecting the content of reactive oxygen species (ROS). Intriguingly, knocking down GSTF2 also rescued the H2O2 hypersensitivity and ROS homeostasis defects in hy5 roots. In addition to H2O2, we showed that hy5 was also hypersensitive to high salinity, Cd, and salicylic acid. Based on these results, we conclude that HY5 plays a positive role in root growth mainly under abiotic stress by modulating both redox homeostasis and oxidative stress response.